Arsenic diffusivity study by comparison of post-Surface and post-implant diffusion in silicon with Local Density Diffusion (LDD-) model approximation - Wirbeleit, Frank (Diffusion Fundamentals, 2011)
The LDD model was first applied to Arsenic concentration profiles determined in surface diffusion experiments by Yoshida and Arai [1]. The new method presented is based on a mathematical convolution with a delta-function-like concentration profile. By comparing the LDD approximation of post-surface diffusion with post-implant diffusion experiments, the same LDD model parameter r is found to hold for both experimental arrangements. This work found that post-implant diffusivity is concentration dependant and this might indicate an anomalous diffusion mechanism for Arsenic.